DETERMINAN KINERJA AUDITOR: STUDI DI WILAYAH JAKARTA SELATAN - Ria Sukmawati; M. Irfan Tarmizi (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2022)
This research aims to obtain empirical evidence regarding the effect of role overload, emotional intelligence, and work-life balance on the performance of auditors with psychological well being as a moderating variable. The research method used is quantitative research. The population in this research were all auditors who worked at the Public Accounting Firm (KAP) in the South Jakarta Region with a total sample of 84 respondents. The sampling technique used is the convenience sampling method. The data source used is primary data. The data collection method used a survey method with a questionnaire. The data analysis method used is multiple linear regression analysis and moderated regression analysis (MRA). The results of this study indicate that role overload does not have a significant effect on auditor performance, while emotional intelligence, work-life balance and psychological well being have a positive and significant effect on auditor performance. The analysis of moderating variables using the MRA approach shows that psychological well being is able to moderate the effect of role overload and emotional intelligence on auditor performance, but not on the effect of work-life balance on auditor performance.